2021
DOI: 10.1080/23311975.2021.1882039
|View full text |Cite
|
Sign up to set email alerts
|

A mediating effect of business growth on zakat empowerment program and mustahiq’s welfare

Abstract: Zakat is an instrument of Islamic economic and social funds that contributes to the achievement of people wellbeing. This study examines the business growth as a mediating variable on the relationship between the impact of the zakat empowerment programs and mustahiq's (zakat recipient) welfare. This quantitative study employs Partial Least Square Structural Equation Modelling (PLS-SEM) analysis on 100 mustahiqs from different zakat empowerment programs in East Java and DI Yogyakarta. Zakat empowerment positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 37 publications
(53 reference statements)
2
49
0
1
Order By: Relevance
“…Sari et al [ 73 ] show that by distributing zakat, the time taken by the poor to exit poverty is faster (3.3 years) than without zakat (6.6 years). In addition, a study conducted by Widiastuti et al [ 3 ] analyzed financing programs carried out by the ISF institutions, including Yatim Mandiri, Dompet Dhuafa, Inisiatif Zakat Indonesia, Nurul Hayat, YDSF, and Dompet Amanah Umat, and found that they have a significant impact on increasing the welfare of the poor. The distribution aspect, particularly productive distribution, holds the key to success in ISF integration in transforming the poor into the capables [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sari et al [ 73 ] show that by distributing zakat, the time taken by the poor to exit poverty is faster (3.3 years) than without zakat (6.6 years). In addition, a study conducted by Widiastuti et al [ 3 ] analyzed financing programs carried out by the ISF institutions, including Yatim Mandiri, Dompet Dhuafa, Inisiatif Zakat Indonesia, Nurul Hayat, YDSF, and Dompet Amanah Umat, and found that they have a significant impact on increasing the welfare of the poor. The distribution aspect, particularly productive distribution, holds the key to success in ISF integration in transforming the poor into the capables [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second instrument is infaq and sadaqah , which are the voluntary gifts by capable people to seek the pleasure of Allah [ 44 ], significantly to help the needy. Zakat, infaq , and sadaqah are economic instruments that support economic growth by increasing the purchasing power of the needy [ 3 , 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations